Extended Performance Research on 5 GHz IEEE 802.11n WPA2 Laboratory Links - Carvalho, José Pacheco de (2019)
Wireless communications by microwaves are increasingly important, e.g. Wi-Fi. Performance is a crucial issue, improving reliability and efficiency in communications. Security is also most important. Laboratory performance measurements are presented for Wi-Fi 5 GHz IEEE 802.11n WPA2 links. Our study contributes to performance evaluation of this technology under WPA2 encryption, using available equipments (HP V-M200 access points and Linksys WPC600N adapters). New results are given, namely for OSI level 4, from TCP and UDP experiments. TCP throughput is measured versus TCP packet length. Jitter and percentage datagram loss are measured versus UDP datagram size. Results are compared for point-to-point, point-to-multipoint and four-node point-to-multipoint links. Comparisons are also made to corresponding data obtained for Open links. Conclusions are drawn about performance of the links. © Springer Nature Singapore Pte. Ltd. 2019